Too Strange for Reality, Too Real for Fairy Tales: Views from Cognitive and Unnatural Narratology on A.S. Byatt’s “A Stone Woman” (ENTHYMEMA, 2020)
In “A Stone Woman” (2003), A.S. Byatt centres the story of her protagonist’s fantastic metamorphosis around the continuities between the transformations involving the body and those affecting the mind. In this light, her narrative constitutes a fictional exploration of cognition as embodied and of language as a cognitive tool equally rooted in embodiment. While this focus straightforwardly calls for second-generation cognitive narratology as the most suitable theoretical framework, the article proposes to integrate the cognitive approach with insights from unnatural narratology. This combined perspective arguably allows to appreciate and examine Byatt’s ambivalent use of embodied cognition as both a shared condition that fosters the readers’ capability to relate to the narrated experience, but also as a strategy that interacts with traditional features of the fairy tale (e.g. the lack of psychological introspection) in ways that are defamiliarizing and yet not subversive of the genre.